Potential of miR-21 to Predict Incomplete Response to Chemoradiotherapy in Rectal Adenocarcinoma - Ourô, Susana; Mourato, Cláudia; Velho, Sónia; Cardador, André; Ferreira, Marisa P.; Albergaria, Diogo; Castro, Rui E.; Maio, Rui; Rodrigues, Cecília M. P. (Frontiers in Oncology, 2020)
Background: Patients with locally advanced rectal adenocarcinoma (LARC) are treated with neoadjuvant chemoradiotherapy (CRT). However, biomarkers for patient selection are lacking, and the association between miRNA expression and treatment response and oncological outcomes is unclear. Objectives: To investigate miRNAs as predictors of response to neoadjuvant CRT and its association with oncological outcomes. Methods: This retrospective study analyzed miRNA expression (miR-16, miR-21, miR-135b, miR-145, and miR-335) in pre- and post-chemoradiation rectal adenocarcinoma tissue and non-neoplastic mucosa in 91 patients treated with neoadjuvant CRT (50.4 Gy) and proctectomy. Two groups were defined: a pathological complete responders group (tumor regression grade—TRG 0) and a pathological incomplete responders group (TRG 1, 2, and 3). Results: miR-21 and miR-135b were upregulated in tumor tissue of incomplete responders comparing with non-neoplastic tissue (p = 0.008 and p < 0.0001, respectively). Multivariate analysis showed significant association between miR-21 in pre-CRT tumor tissue and response, with a 3.67 odds ratio (OR) of incomplete response in patients with higher miR-21 levels (p = 0.04). Although with no significance, patients treated with 5-fluorouracil (5-FU) presented reduced odds of incomplete response compared with those treated with capecitabine (OR = 0.19; 95% confidence interval (CI) 0.03–1.12, p = 0.05). Moreover, significant differences were seen in overall survival (OS) in relation to clinical TNM stage (p = 0.0004), cT (p = 0.0001), presence of distant disease (p = 0.002), mesorectal tumor deposits (p = 0.003), and tumor regression grade (p = 0.04). Conclusion: miR-21 may predict response to CRT in rectal cancer (RC).